From sub-individual responses to ecological risk through an integrative framework based on the Health Status Index linking biochemical disruption to functional impairment in Ruditapes decussatus exposed to barium chloride - Zeineb Khila; Nejla Soudani; Simon Devin (Environmental Pollution, 2026)

Linking oxidative stress and lipid remodeling in Palaemon adspersus exposed to barium chloride: Evidence from EC50, BMD and PLS-PM modeling - Zeineb Khila; Maximilien Beuret; Boutheina Ben Abdallah; Dalya Belhassen; Nejla Soudani; Simon Devin (Marine Pollution Bulletin, 2026)

Tissue concentration, mortality, and response of subcellular biomarkers in Dreissena polymorpha exposed to nickel: absence of dose-response relationships for biomarkers despite dose-dependent toxicity - Manon Bain; Sandrine Pain-Devin; Bénédicte Sohm; Chloé De Vernisy; Simon Devin (Aquatic Toxicology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Environmental observation and monitoring through space and time: a challenge for ecotoxicology - Sandrine Pain-Devin; Simon Devin (Environmental Science and Pollution Research, 2025)

New insight into barium toxicity in the gills of the European clam (Ruditapes decussatus): a focus on redox status, fatty acids profiles, and histological structures - Zeineb Khila; Wafa Trabelsi; Safa Bejaoui; Maximilien Beuret; Dalya Belhassen; Boutheina Ben Abdallah; Simon Devin; Nejla Soudani (Aquatic Sciences, 2025)

Impact of dye treatment as management strategy on available light may favour a highly invasive alien aquatic plant - Hélène Groffier; Mohamed A. Mahdjoub; Simon Devin; Elisabeth M. Gross (Aquatic Botany, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Fate, subcellular distribution and biological effects of rare earth elements in a freshwater bivalve under complex exposure - Nicolas Lachaux; Alba Otero-Fariña; Laetitia Minguez; Bénédicte Sohm; Julie Rétif; Amélie Châtel; Laurence Poirier; Simon Devin; Sandrine Pain-Devin; Elisabeth M. Gross; Laure Giamberini (Science of The Total Environment, 2023)

Characterization of the impact of chlorogenic acids on tactile perception in coffee through an inverse effect on mouthcoating sensation - Brianne M. Linne; Edisson Tello; Christopher T. Simons; Devin G. Peterson (Food Research International, 2023)

Spatial and seasonal use of biomarkers in dreissenids: implications for biomonitoring - Simon Devin; Marine Potet; Fanny Louis; Danièle Pauly; Béatrice Rocher; Philippe Wagner; Laure Giambérini; Sandrine Pain-Devin (Environmental Science and Pollution Research, 2023)

Correction to: CalIBRi: a web interface to calculate Integrated Biomarker Index - Simon Devin; Pierre-Yves Arnould; Laetitia Minguez; Sandrine Pain-Devin; Virginie Jouffret (Environmental Science and Pollution Research, 2023)

Assessing the effects of silver nanoparticles on the ecophysiology of Gammarus roeseli - Jennifer Andreï; François Guérold; Jonathan Bouquerel; Simon Devin; Kahina Mehennaoui; Sebastien Cambier; Arno C. Gutleb; Laure Giambérini; Sandrine Pain-Devin (Aquatic Toxicology, 2023)

Time for speciation and niche conservatism explain the latitudinal diversity gradient in clupeiform fishes - Joshua P. Egan; Devin D. Bloom; Andrew M. Simons (Journal of Biogeography, 2022)
Aim The latitudinal diversity gradient of increasing species richness from poles to equator is one of the most striking and pervasive spatial patterns of biodiversity. Climate appears to have been key to the formation of the latitudinal diversity gradient, but the processes through which climate shaped species richness remain unclear. We tested predictions of the time for speciation, carrying capacity and diversification rate latitudinal diversity gradient hypotheses in a trans‐marine/freshwater clade of fishes. Location Global in marine and freshwater environments. Taxon Clupeiformes (anchovies, herrings, sardines and relatives). Methods We tested predictions of latitudinal diversity gradient hypotheses using a molecular phylogeny, species distribution data and phylogenetic comparative approaches. To test the time for speciation hypothesis, we conducted ancestral state reconstructions to infer the ages of temperate, subtropical and tropical lineages and frequency of evolutionary transitions between climates. We tested the carry capacity hypothesis by characterizing changes in net diversification rates through time. To test the diversification rate hypothesis, we qualitatively compared the diversification rates of temperate, subtropical and tropical lineages and conducted statistical tests for associations between latitude and diversification rates. Results We identified four transitions to temperate climates and two transitions out of temperate climates. We found no differences in diversification rates among temperate and tropical clupeiforms. Net diversification rates remained positive in crown Clupeiformes since their origin ~150 Ma in both tropical and temperate lineages. Climate niche characters exhibited strong phylogenetic signal. All temperate clupeiform lineages arose Main conclusions Our results support the time for speciation hypothesis, which proposes that climate niche conservatism and fluctuations in the extent of temperate climates limited the time for species to accumulate in temperate climates, resulting in the latitudinal diversity gradient. We found no support for the carrying capacity or diversification rate hypotheses.

Impacts of chemical stress, season, and climate change on the flounder population of the highly anthropised Seine estuary (France) - Jennifer Laurent; Edouard Lavergne; Jérôme Couteau; Stéphane Le Floch; Baghdad Ouddane; Jérôme Cachot; Blandine Davail; Christelle Clérandeau; Simon Devin; Cédric Fisson; Alain Devaux; Rachid Amara; et al. (Environmental Science and Pollution Research, 2022)

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Examining progress towards achieving the Ten Steps of the Rome Declaration on Responsible Inland Fisheries - Abigail J. Lynch; Devin M. Bartley; Thomas Douglas Beard; Ian G. Cowx; Simon Funge‐Smith; William W. Taylor; Steven J. Cooke (Fish and Fisheries, 2020)
Inland capture fisheries provide food for nearly a billion people and are important in the livelihoods of millions of households worldwide. Although there are limitations to evaluating many of the contributions made by inland capture fisheries, there is growing recognition by the international community that these services make critical contributions, most notably to food security and livelihoods in rural populations in those low‐income countries with extensive freshwater resources. With the increasing appreciation of the key role of inland fisheries to the health and well‐being of human populations globally, the Food and Agriculture Organization of the United Nations and Michigan State University convened the 2015 global conference, Freshwater, fish, and the future – cross‐sectoral approaches to sustain livelihoods, food security, and aquatic ecosystems . What emerged from the interactions between inland fisheries’ scientists, resource managers, policymakers and community representatives from across the world was a forward‐looking call to action culminating with the 2015 Rome Declaration “Ten Steps to Responsible Inland Fisheries” (FAO & MSU, Rome declaration on responsible inland fisheries: 5735E/1/06.16 ). Four years after this landmark conference and declaration, we seek to advance discussion on the “Ten Steps,” namely what successful implementation looks like, assess current examples of implementation, suggest potential signals of progress and provide some specific, indicative examples of progress for each step. While there are promising signs of progress, we conclude that there remains a strong need to galvanize momentum for sustained action to ensure that inland fish and fisheries are accounted for and incorporated into broader water resource management discussions and frameworks.

Corbicula fluminea gene expression modulated by CeO2 nanomaterials and salinity - Vanessa Koehlé-Divo; Sandrine Pain-Devin; Carole Bertrand; Simon Devin; Catherine Mouneyrac; Laure Giambérini; Bénédicte Sohm (Environmental Science and Pollution Research, 2019)

Effects of increasing temperatures on biomarker responses and accumulation of hazardous substances in rope mussels (Mytilus galloprovincialis) from Bizerte lagoon - Naouel Kamel; Thierry Burgeot; Mohamed Banni; Mohamed Chalghaf; Simon Devin; Christophe Minier; Hamadi Boussetta (Environmental Science and Pollution Research, 2014)

Benthic indicators of sediment quality associated with run-of-river reservoirs - Colas Fanny; Archaimbault Virginie; Férard Jean-François; Bouquerel Jonathan; Roger Marie-Claude; Devin Simon (Hydrobiologia, 2013)

Geographic patterns in freshwater gammarid invasions: an analysis at the pan-European scale - Simon Devin; Jean-Nicolas Beisel (Aquatic Sciences, 2008)

Biological and ecological characteristics of invasive species: a gammarid study - Simon Devin; Jean-Nicolas Beisel (Biological Invasions, 2006)

Patterns of Biological Invasions in French Freshwater Systems by Non-Indigenous Macroinvertebrates - Simon Devin; Loïc Bollache; Pierre-Yves Noël; Jean-Nicolas Beisel (Hydrobiologia, 2005)

Changes in functional biodiversity in an invaded freshwater ecosystem: the Moselle River - Simon Devin; Jean-Nicolas Beisel; Philippe Usseglio-Polatera; Jean-Claude Moreteau (Hydrobiologia, 2005)